A study on the optimum insulation thicknesses of various types of external walls with respect to different materials, fuels and climate zones in Turkey - Ekici, Betul Bektas; Gulten, Ayca Aytac; Aksoy, U. Teoman (Elsevier Sci Ltd, 2012)
In Turkey the insulation of buildings was not a common occurrence until it became obligatory after the publication of the TS 825 Turkish Thermal Insulation Standard. However, most of the buildings still have little or no insulation. The aim of this study is to show the optimum insulation thicknesses for the different wall types; stone, brick and concrete, which are usually used in building construction in Turkey. Four cities from different climate zones, determined by the Turkish Thermal Insulation Standard (TS 825); Antalya (1st zone), Istanbul (2nd zone), Elazig (3rd zone) and Kayseri (4th zone) were selected for analysis, and the optimum insulation thicknesses, energy savings and payback periods were calculated for each. Fiberglass, extruded polystyrene, expanded polystyrene and foamed polyurethane were the chosen insulation materials. The calculations were carried out with five different energy types; coal, LPG, electricity, fuel oil, and natural gas. As a consequence the results show that the optimum insulation thickness varies between 0.2 cm and 18.6 cm, energy savings vary between 0.038 $/m(2) and 250.415 $/m(2), and payback periods vary between 0.714 and 9.104 years depending on the city, the type of wall, the insulation material and the cost of fuel. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Insulation; Optimum insulation thickness; Energy saving; Life cycle cost; Payback period